Indirect Impact of COVID-19 Lockdown on Society and Environment - Radha Andhare1, Yogita Shrivas2, Shubhada Guru3, Abhishek Joshi4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In a fairly short time, the worldwide spread of COVID-19 has brought a dramatic reduction in industrialactivities, road traffic and tourism. During this time of crisis restrained human interaction with naturehas appeared as a blessing for nature and the environment. Reports from around the world indicate thatenvironmental conditions, including air quality and water quality in rivers, are improving after the COVID-19outbreak, and wildlife is blooming. India has always been a pollution hub with enormous populations. Butsince COVID-19 announced the lockdown, air quality has begun to improve and all other environmentalparameters such as water quality in rivers have begun to offer a positive sign of restoration